Profil en imagerie par résonance magnétique de la pathologie du genou à Ouagadougou - ZANGA Soré Moussa; DAO Siaka Ben Aziz; OUATTARA Boubacar; SOME Christian; BAMOUNI Yomboué Abel; CISSE Rabiou (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2022)
Objectives: To assess the contribution of Magnetic Resonance Imaging (MRI) in the diagnostic assessment of knee pathologies in the city of Ouagadougou. Materials and methods: This was a retrospective study with a descriptive aim on knee pathologies during the period from January 1st, 2016 to August 31, 2016. It consisted to analyse the MRI reports examinations of the knee carried out in three health structures in the city of ouagadougou during the same period Results: There was a male predominance with a sex-ratio of 1,7. The age group of 25 to 50 years was the more represented with 66,6% cases. The reason of exploration were dominated by the instability of the knee in 52 cases (38%), the knee chronic pain in 47 cases (34,4%) and acute knee pain in 38 cases (27,7%). The main mechanism of the knees injury was traumatic in 80,3%. The examinations protocols used were essentially the T1, T2 weighted spin echo sequences and proton density sequences with or without fat saturation. The main lesions were meniscal (58,4%), followed by the central pivot injury (57,7%), bony lesions (43,1%) and cartilaginous lesions (34,3%). Conclusion: MRI is the best exam to explore precisely the complex knee joint. It can detect bone and joint lesions, the diagnosis of which was previously uncertain with standard radiography, ultrasound or computed tomography (CT). These lesions are dominated by those of the menisci and the central pivot. The most frequent indications were dominated by knee instability and post-traumatic knee pain. RESUME Objectif : Déterminer l’apport de l’imagerie par résonance magnétique (IRM) dans le bilan diagnostique des pathologies du genou dans la ville de Ouagadougou. Matériels et méthodes : Il s’est agi d’une étude rétrospective à visée descriptive sur les pathologies du genou durant la période du 1er janvier 2016 au 31 août 2016. Elle a consisté en l’analyse des comptes rendus d’examens d’IRM du genou réalisés dans trois structures sanitaires de la ville de Ouagadougou durant la même période. Les protocoles d’examen utilisés étaient essentiellement les séquences en écho de spin pondérée en T1, T2 et en densité de proton avec ou sans saturation de graisse. Résultats : les patients de sexe masculin étaient prédominants avec un sex-ratio de 1,7. La tranche d’âge de 25 à 50 ans était la plus représentée avec 66,6% des cas. Les indications des demandes d’examen étaient dominées par l’instabilité du genou dans 52 cas (38%), la gonalgie chronique dans 47 cas (34,4%) et la gonalgie aigüe dans 38 cas (27,7%). Dans 80,3% des cas, le mécanisme lésionnel était le traumatisme. Les principales anomalies étaient les lésions méniscales (58,4%), suivies des lésions du pivot central (57,7%), des lésions osseuses (43,1%) et des lésions cartilagineuses (34,3%). Conclusion : L’IRM est l’une des meilleures techniques d’imagerie permettant d’explorer de manière précise l’articulation du genou. Les principales anomalies étaient les lésions des ménisques et celles du pivot central ; les indications les plus fréquentes étaient dominées par l’instabilité du genou et les gonalgies post traumatiques.